Reimagining Nepali Nationhood: Challenging the Dominant National Narratives in Nepali Poetry of Indigenous Consciousness - Rai, Prakash (The Journal of Nuwakot Adarsha Multiple Campus, 2025)
Nepal’s dominant national narrative has historically been shaped by the upper caste Hindu ruling elite, who institutionalized their cultural ideology through state mechanisms, literature, and education. This monolithic construction of nationhood has long marginalized ethnic indigenous communities, particularly the Kirant – Rai and Limbu, whose cultural and religious practices challenge the hegemony of the state. In this context, the paper examines how Anjana Ichhamphul’s “A Tale of Spoiled Dream” and Naresh Kangmang’s “Mr. Poet, My Poem will be Burnt with Your Hand” contest Nepal’s majoritarian national discourse by foregrounding the lived experiences, spirituality, and cultural agency of the Kirant people. Drawing upon the postcolonial perspectives such as “the performative and pedagogical narratives of the nation” by Homi K. Bhabha, and the idea “epistemic violence” by Gayatri Chakravarty Spivak, the study explores how Nepali poetry of ethnic voice reimagines Nepal as pluralistic nation grounded in mutual recognition and coexistence rather than conflict and hierarchical domination. The findings of the research contribute to the existing scholarship and Nepali society in three tiers: literary discourse in postcolonial context functions as site for reimaging inclusive nation; ethnic reconciliation emanated from cultural recognition rather than assimilation; and reinterpreting nationalism through plural consciousness fosters sustainable democratic identity formation.